A comparison of shear bond strength of immediate and delayed bonding of brackets to FRC bars using various orthodontic adhesives - Heravi Farzin; Moazzami Saied Mostafa; Kerayechian Navid; Nik Elham (Sciendo, 2011)
Background: Fibre reinforced composite bars (FRC) have applications as bonded retainers, space maintainers and anchorage/movement units. However, the bond strength of attachments to FRC anchorage bars is unknown.